UPAYA MENGATASI KEBOCORAN PENERIMAAN RETRIBUSI RUMAH POTONG HEWAN PADA UPACARA ADAT RAMBU SOLO’ KELURAHAN TONGKO SARAPUNG KECAMATAN SANGALLA’ KABUPATEN TANA TORAJA - Saba’ Sombolinggi; Kristian H.P. Lambe; Corvis L. Rantererung (Paulus Journal of Accounting (PJA), 2024)
This study discusses efforts to overcome leakage of Slaughterhouse Retribution (RRPH) revenues during the Rambu Solo' Traditional Ceremony in Tongko Sarapung Village, Sangalla District, Tana Toraja Regency. Leakage of retribution is a problem that has an impact on Regional Original Income (PAD), caused by compromises between collectors and taxpayers, lack of transparency, and ineffective collection mechanisms. This study uses a descriptive qualitative approach through observation and in-depth interviews with various related parties. The results of the study indicate that innovation in payment digitalization, increased supervision, and socialization of regulations can increase public compliance in paying retribution. The implementation of the QRIS system, transparency in recording receipts, and the contribution of local governments in supporting the implementation of traditional ceremonies can be effective strategies in reducing leakage of retribution revenues.